Identifying Drivers and Barriers in The Involvement Of Integrated Township as an E-Waste Collection Hub: a Dematel-Based Anp Approach - Faraz JANATRA; Romadhani ARDI (International Journal of Environmental, Sustainability, and Social Science, 2025)
The growth of urbanization in Indonesia has led to a significant increase in waste generation, including e-waste, which has a negative impact on the environment if not managed properly. Independent cities, as integrated areas with modern infrastructure, have the strategic potential to become hubs for e-waste collection. However, his involvement is still minimally studied. This study aims to identify and analyze the driving and inhibiting factors of independent city involvement in e-waste collection, as well as determine the cause-and-effect relationship and priority of each factor using the Content Validity Index (CVI), Modified Kappa, DEMATEL, and Analytic Network Process (ANP) methods. The results of the analysis showed that, among the driving factors, the Population dimension (HD) had the highest level of interconnectedness, while the Government dimension (GD) exhibited the greatest net influence. On the other hand, in the inhibiting factor, the Developer (DB) dimension has the highest level of relevance, while the Collector (CB) dimension has the greatest net influence, with the Government (GB) dimension also showing significant linkage and net influence values. In terms of weight, the primary driving factors were public acceptance of the collection program (0.094), the level of environmental knowledge (0.082), and government supervision (0.082). Meanwhile, the main inhibiting factors include the population's lack of waste sorting (0.087), tax policies that do not support collectors (0.084), and the absence of government collection standards (0.082).